Faktor Determinan Tekanan Finansial Pada Generasi Z Di Kota Tasikmalaya - Nur Arbaien, Muhamad Fasya; Nurkaromah, Silvia Ripa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to measure the factors that cause financial pressure on Gen Z in Tasikmalaya City. The research used quantitative methods with structural equation modeling approach. The results show that financial literacy and financial behavior hurt financial stress. This means that the higher the financial literacy and behavior index, the lower the financial pressure. However, lifestyle has a direct effect on financial stress. The higher the lifestyle, the higher the financial pressure that Gen Z receives.